First report of Syneura cocciphila (coquillett, 1895) (Diptera : Phoridae), as a predator of the fluted scale Crypticeria multicicatrices Kondo & Unruh, 2009 (Hemiptera : Monophlebidae) - Gaimari, Stephen D.; Quintero Q., Edgar Mauricio; Takumasa, Kondo (Universidad del Valle, 2025)
Since 2010, the multicicatrices fluted scale Crypticerya multicicatrices Kondo & Unruh (Hemiptera: Monophlebidae: Iceryini) has been reported as a serious pest attacking numerous plants including palms, various fruit trees and ornamental plants on the island of San Andres, Colombia (ICA 2010), and more recently on the neighboring island of Providencia (Kondo et al. 2012). According to Kondo et al. (2012), the multicicatrices fluted scale was introduced into the islands of San Andres and Providencia, probably through infested ornamental plants brought from mainland Colombia where the insect is endemic to. Besides an entomopathogenic fungi, Paecilomyces sp. (Quiroga et al. 2011)